The Impact of Re-Infection With COVID-19 on Human Immunity and Coping Strategies in The Post-Pandemic Era - Zhang, Xinyuan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The COVID-19 pandemic, caused by SARS-CoV-2, has led to over 6.9 million deaths as of August 2024 as a significant global health threat. While advancement of vaccines and drugs targeting SARS-CoV-2 virus has reduced severe illness, reinfection remains a significant concern. This paper explores the impact of COVID-19 reinfection on human immunity and examines possible coping strategies, particularly the advancements in plant-derived adjuvants to enhance vaccine efficacy. The virus’s ability to mutate, evade immune responses, and affect immune memory highlights the importance and potential effectiveness of treatments that prolong immunity response. Plant-derived adjuvants Advax and Matrix-M have been shown to improve long term immune responses by stimulating long-lasting antibodies and cytotoxic T-cell activation. Clinical trials have demonstrated efficacy and safety in preventing symptomatic and severe COVID-19, along plant-based adjuvants reducing reinfection risks. Future research could further focus on develop precising adjuvants’ formulations, exploring more plant-based compounds that could be apply in vaccine development, and conducting long-term studies to evaluate long-term immune durability and safety of the vaccines.